1931
DOI: 10.5962/bhl.title.82146
|View full text |Cite
|
Sign up to set email alerts
|

Animal motivation : experimental studies on the albino rat /

Abstract: COLUMBIA OBSTRUCTION METHOD pie) and, with equally easy access to both, supposedly goes to the one having the highest incentive value at the moment. It is difficult to say who first applied this type of test, but certainly it has been used extensively by various workers on lower forms in approaching the problem of the relative potency of tropisms, and of instincts under different conditions. The literature of the last several decades contains so many studies of this sort that it is hardly necessary to cite spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

1966
1966
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…Later, Nissen (1930) and Warden (1931), employing electric grid obstruction apparatus, found that mother rats would perform more grid crossings to get to their litters than they would when the reinforcement was satiation of thirst, hunger, sex, or exploration. Curiously, no reports have yet related this maternal motivation to the classical bar-pressing situation.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Nissen (1930) and Warden (1931), employing electric grid obstruction apparatus, found that mother rats would perform more grid crossings to get to their litters than they would when the reinforcement was satiation of thirst, hunger, sex, or exploration. Curiously, no reports have yet related this maternal motivation to the classical bar-pressing situation.…”
Section: Resultsmentioning
confidence: 99%
“…Barnea-Ygael et al (2012) used a conflict-based relapse model (Cooper et al, 2007) to assess the time course of cue-induced cocaine seeking after suppression of cocaine self-administration by an electric barrier (Warden, 1931). During tests for cue-induced relapse 1 or 14 days after the last electric barrier session, rats were tested in the presence of the barrier.…”
Section: Incubation Of Methamphetamine and Food Craving After Punishmentmentioning
confidence: 99%
“…To mimic the aversive components of the drug seeking period, we have begun to develop a conflict model of relapse. The basic concept of this model is similar to that of the 'Columbia Obstruction Box' method, which has been used many years ago to assess rats' motivation to obtain rewards under different deprivation conditions in the presence of an 'electric barrier' (Jenkins et al 1926;Olds and Olds 1958;Warden 1931). Our model was also inspired by results of more recent studies in which motivation to seek and take drugs was assessed in the presence of aversive stimuli (Deroche-Gamonet et al 2004;Vanderschuren and Everitt 2004;Wolffgramm and Heyne 1995).…”
mentioning
confidence: 99%